How Did We Get Here? An Examination of Opioid Addiction from A Historical Perspective - Gallo, Ralph (Advances in Social Sciences Research Journal, 2021)
America is facing a drug crisis that is rocking the nation at the cost of one trillion dollars since former President Richard Nixon declared war on drugs more than 40 years ago in 1971. This latest opioid crisis can be identified as the war on drugs 2.0. Research supports that the American public is not interested in fighting the war on drugs; it is interested in creating viable intervention programs that are effective in treating drug addiction and education programs for the drug prescribing medical community. Results revealed statistically significant differences between socioeconomic status and race, family status and criminal background, family status and criminal background related to a drug background, and family status and equally offering drug treatment options.